Korea's Participation in Global Value Chains: Measures and Implications - Sung Hoon Chung (KDI Journal of Economic Policy, 2016)
This paper measures the extent to which South Korea participated in global value chains (GVCs) from 1995 through 2011 and scrutinizes the consequences of such participation on the Korean economy. To this end, the World Input Output Database is utilized to calculate GVC income, GVC employment, and value-added exports created by Korean and foreign industries. Our findings show that Korea radically internationalized its production activities during the sample period, widening the gap between gross exports and value-added exports. We also document that Korea's participation in GVCs has changed the value-added and employment structures in domestic industries in accordance with their comparative advantages while exacerbating the degree of wage inequality.
Keywords: F10; F21; F23; 330; Global Value Chain; GVC; Trade in Value Added; GVC Income; GVC Employment; International Fragmentation of Production